2018
DOI: 10.1029/2018pa003397
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Model Bias on Simulating North Atlantic Sea Surface Temperature During the Mid‐Pliocene

Abstract: Climate models generally underestimate the pronounced warming in the sea surface temperature (SST) over the North Atlantic during the mid‐Pliocene that is suggested by proxy data. Here we investigate the influence of the North Atlantic cold SST bias, which is observed in many climate models, on the simulation of mid‐Pliocene surface climate in a series of simulations with the Kiel Climate Model. A surface freshwater‐flux correction is applied over the North Atlantic, which considerably improves simulation of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Recent terrestrial mPWP data-model comparisons highlight that PlioMIP2 models cannot reproduce the full extent of the mPWP warming that data suggest ( 2 , 21 , 44 ). Likewise, in both the pelagic and terrestrial realm, reconstruction of the full seasonal cycle is challenging due to proxy limitations ( 2 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent terrestrial mPWP data-model comparisons highlight that PlioMIP2 models cannot reproduce the full extent of the mPWP warming that data suggest ( 2 , 21 , 44 ). Likewise, in both the pelagic and terrestrial realm, reconstruction of the full seasonal cycle is challenging due to proxy limitations ( 2 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…6). Previous studies (Brierley and Fedorov, 2016;Otto-Bliesner et al, 2017;Song et al, 2018) showed that the closing of the Arctic gateways led to warmer North Atlantic SSTs in the mid-Pliocene experiment, when compared to the pre-industrial level. However, the Arctic gateways are closed in all PlioMIP2 simulations analysed here, but not all of them simulate the warm North Atlantic SSTs as reconstructed in the PRISM4 data set (Foley and Dowsett, 2019).…”
mentioning
confidence: 95%
“…The PlioMIP1 simulations (e.g. Chan et al, 2011;Bragg et al, 2012;Contoux et al, 2012;Kamae and Ueda, 2012;Stepanek and Lohmann, 2012;Zhang et al, 2012;Chandler et al, 2013;Rosenbloom et al, 2013) showed that the global annual mean surface air temperature (SAT) was 1.9-3.6 • C warmer than the pre-industrial level in the multi-model ensemble mean (Haywood et al, 2013), whereas the strength of Atlantic Meridional Overturning Circulation (AMOC) was similar to the pre-industrial level (Zhang et al, 2013a). However, when compared to marine (Dowsett et al, 2012(Dowsett et al, , 2013 and terrestrial reconstructions (Salzmann et al 2013), there was a large model-data discrepancy (Haywood et al, 2013) in the North Atlantic and the land realm of the Northern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation